The Kinetics of Cell-Free DNA in Response to External and Internal Factors (Baltic Journal of Sport and Health Sciences, 2025)
Background and objectives: To assess the inflammatory response or muscle damage after exercise, researchers commonly use numerous physiological markers such as creatine kinase (CK), interleukins, and a reduction in muscle function (Souglis et al., 2015; Kamandulis et al., 2021). However, the sensitivity of most of these markers is inadequate for detecting various physiological events such as fatigue, overtraining, muscle damage, adaptation, acute or delayed inflammation. Cell-free DNA (cfDNA) stands as a potential biomarker for assessing exercise load and ensuring training regimes are appropriately tailored to an athlete’s capacity. By monitoring cfDNA, practitioners can identify individuals at risk of overtraining and implement interventions to prevent chronic fatigue and address recovery needs. cfDNA in sports science is in its infancy, yet its short half-life and high sensitivity make it an attractive biomarker (Fatouros et al., 2006; Tug et al., 2017). The general aim of the dissertation was to determine the impact of different internal and external instances, such as 3-week sprint interval training (SIT), increased rectal temperature, and muscle-damaging exercise, on cfDNA kinetics. Methods: Three studies were conducted. Study 1 included nine sessions (three sessions per week over three weeks) of 4–6 cycling bouts (Wingate tests) lasting for 30 s, with 4 min recovery intervals between bouts. In Study 2, each participant completed exertional heating (cycling at 60% V̇O2max until rectal temperature (Tre) reached 39°C) and exogenous heating (lower-body immersion in hot water until Tre reached 39°C) in a randomised cross-over design. There were three groups in Study 3, where each group performed a different number of drop jumps (DJ) (50, 25, 10) at intervals of one every 20 s. All measurements were performed as follows:• Study 1 (subjects: young healthy men (n = 10), elderly healthy men (n = 9): Blood samples for cfDNA and lactate were taken, and neuromuscular testing was done after the first and last session. Measurements were done before, post-exercise, post 1 h, and post 24 h.• Study 2 (subjects: young healthy men (n = 12): Every increase in Tre of 0.5°C up to 39°C and down to 37.5°C, parameters were documented, including subjective sensation, cardiovascular status, Tre, and blood samples were collected.• Study 3 (subjects: young healthy men (DJ-50 group = 14, DJ-25 group = 7, DJ-10 group = 4): Measurements (blood samples, neuromuscular testing, assessment of muscle pain) were done starting from 15 min pre-exercise until several time points to 96 h post-exercise. Results: In Study 1, only young participants exhibited a significant increase in V̇O2max after three weeks of SIT (p = 0.0039). The plasma cfDNA concentration increased significantly (p